Pengaruh Kualitas Kehidupan Kerja dan Lingkungan Kerja terhadap Komitmen Organisasi Karyawan (Studi Pada Divisi Peralatan Industri Agro PT. Barata Indonesia (Persero) Gresik ) - Rahmita Devi Maharani (BISMA (Bisnis dan Manajemen), 2018)
Human resources is the most important elements in order to operating all resources on the company. And the point is ; (1) Quality of worklife is a level where the member of the organization can satisfy the important personal requirement through the experience on the task in the organization. (2) Work environment is a everything around the employee and can influence the employee doing the job. Also with (3) organizational commitment is a personal identification degree to the organization and a will to continue the participation on organization. The purpose of this research is to know about the influence of the quality of worklife and work environment to the effect of commitment organization on Agro Industrial Tool Division  PT Barata Indonesia (Persero) Gresik, and to know how great the influence quality of worklife and work environmnet toward organizational commitment of the employee on Agro Industrial Tool Division  PT Barata Indonesia (Persero) Gresik. On this research we using the quantitatif research aproach, the variable on this research is a free variable (X1), is a quality of worklife and (X2) work environment, and also organizational commitment (Y). The research sample is 68 of Agro Industrial Tool Division PT Barata Indonesia (Persero) Gresik employee. The data collecting is over observation, spreading questioner, documentation, intervewing, and book study. Data analysis doing with double linear regresion, test (F) and test (t). From the analysis result we can get double linear regresion equation : Y = 2.520 + 0.188 x1 +0.157 x2 + Îµi, from the calculation, the coeffisien determination value is 69.2%. 69.2% variation both of independent variable is quality of worklife and work environment. And the 30.8% is explained of the other factor that not become the independent variable on this research. Based of the test result (f), with value 3.372 > from F(0.05;2;65)  (3.14), and sign value < (0.05), with the result that H0 rejected and Ha accepted. For (t) test with value for  is 2.364 > 1.671, and value for  adalah 2.114 > 1.670. This means the influence quality of worklife toward organizational commitment can accepted and the influence of the work environment toward organizational commitment can accepted. The conclusion of this research is quality of worklife and work environment have significant influence to organizational commitment